Antibiofilm effect of Nocardiopsis sp. GRG 1 (KT235640) compound against biofilm forming Gram negative bacteria on UTIs. (May 2018) - Rajivgandhi, Govindan; Vijayan, Ramachandran; Maruthupandy, Muthuchamy; Vaseeharan, Baskaralingam; Manoharan, Natesan
Abstract: Urinary tract infections (UTIs) are diverse public health complication and caused by range of pathogens, however mostly Gram negative bacteria cause significant life threatening risks to different populations. The prevalence rate and antimicrobial resistance among the Gram negative uropathogens alarmed significantly heighten the economic burden of these infections. In this study, we investigated the antibiofilm efficiency of Pyrrolo [1, 2-a] pyrazine-1, 4-dione, hexahydro-3-(2-methylpropyl) extracted from endophytic actinomycetes Nocardiopsis sp. GRG 1 (KT235640) against P. mirabilis and E. coli. The extracted compound was characterized through TLC, HPLC, GC-MS, LC-MS and confocal laser scanning microscopy (CLSM), scanning electron microscopy (SEM). The compound, Pyrrolo [1, 2-a] pyrazine-1, 4-dione, hexahydro-3-(2-methylpropyl) inhibits both bacterial biofilm formation as well as reduces the viability of preformed biofilms. Furthermore, CLSM image shows cell shrinkage, disorganized cell membrane and loss of viability. The SEM result also confirms the cell wall degradation in treated cells of the bacteria. Hence, the Pyrrolo [1, 2-a]pyrazine-1, 4-dione, hexahydro-3-(2-methylpropyl) is active against P. mirabilis and E. coli . Graphical abstract: Highlights: Purification and identification of anti-biofilm compound from Nocardiopsis sp. Anti-QS activity of purified compound for Chromobacterium violaceum. Quantification of anti-biofilm activity against uropathogens of P. mirabilis and E. coli . Detection and morphological alteration of uropathogens by CLSM, SEM.